Expediency of multimedia encyclopedias as a supplementary reference tool for general education courses in the University of the Philippines Diliman - Tecson, Angelo DV (School of Library and Information Studies, University of the Philippines Diliman, 2000)
The aim of this study was to determine the practicality of the multimedia encyclopedia as a supplementary reference tool for students and teachers covered by the General Education Program of University of the Philippines Diliman.